Istiratijiyatu Ta'allum al-Lughah al-Arabiyyah biwasfiha Lughah Ajnabiyah 'Inda al-Talamidz fi al-Madrasah al-Tsanawiyah al-Islamiyah al-Hukumiyyah 1 Banjar 'Abra Ikhtilaafi al-Jinsi wa al-Syu'bah - - Nurul Wahdah (Universitas Negeri Malang, 2017)
This causal comparative study aims at finding out the language learning strategies (LLS) in Arabic as a foreign language used by students across gender and majors at State Islamic Senior High School 1 Banjar, South Kalimantan, Indonesia. There were 127 (one hundred and twenty seven) students who were asked to participate in this study. The instruments were adapted from The Strategy Inventory for Language Learning (SILL) proposed by Oxford (1990). In analysing data, arithmetic mean, deviation standard and independent sample test were used. The results of the study revealed that 1) the most popularly strategy used by students at State Islamic Senior High School 1 Banjar was metacognitive, 2) there is a significant difference in using Arabic language learning strategies between female and male students with p=0.017 ≤ 0.05, 3) there is a significant difference in using Arabic language learning strategies between and between social science major and natural science major students with p=0.02 ≤0.05. This indicated that the differences across gender and majors in using language learning strategies (LLS) in Arabic as a foreign language are found.Keywords: Language learning Strategies, Arabic as foreign language, and gender and majors difference.